Analysis of Type of Delivery and Birth Weight with the Occurrence of Neonatal Jaundice in the Regional Hospital of Merauke Regency - Dwi Muryanti,; Riza Tsalasatul Mufida,; Miftakhur Rohmah,; Retno Palupi Yonni Siwi, (Journal of Health Science Community, 2024)
Neonatal jaundice is caused by maternal, perinatal and neonatal factors. The high incidence of jaundice in the Merauke Regency Regional Hospital is of concern to researchers to determine the relationship Type of Delivery and Birth Weight with Neonatal Jaundice. This research method uses this type of research analytical observational using register measuring instruments in the Perinatal and Medical Records Room with research design cross-sectional and techniques total sampling. The population of this study is Babies aged 0-28 days who experience neonatal jaundice and are treated in the Perinatal Room of the Merauke District Hospital from January to October 2023 as many as 91 respondents, the sample is the same as the population. Statistical test using chi square to find out the relationship between 2 variables. Research results from 91 respondents were obtained The majority of respondents' birth types were at risk of developing neonatal jaundice, 54 respondents (59.3%), the majority of respondents' birth weight was LBW, 58 respondents (63.7%), and the majority of respondents experienced neonatal jaundice, 84 respondents (92, 3%). Analysis using tests Chi-Square for the type of delivery the results were obtained p = 0.003 (< 0.05) and for birth weight the value obtained p = 0.001 (< 0.05) so it can be concluded that there is a relationship between type of delivery and birth weight with the incidence of neonatal jaundice in the Merauke Regency Hospital. It is recommended that delivery and care of newborns is very important by providing motivation or counseling to the mother post caesarean section and vaginal to immediately breastfeed the baby intensively so that these risk factors do not occur which result in neonatal jaundice.